Funkcjonowanie i rozwój aglomeracji miejskich w kontekście możliwości zwiększenia dochodów budżetowych na przykładzie regionu szczecińskiego - Dylewski, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the paper there are some questions and problems considered if it is possible to use progress methods and techniques of budgeting for raising the competitiveness of our cities. It appears, that program budgeting is one of the planning methods of budget which enables to increase the efficiency of public expenditures. A proper allocation of public resources is one of important factors that raise the attractiveness and competitiveness of Polish metropolis. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 67-74